ЗБЕРЕЖЕННЯ ТА ГЕНЕЗА СОЦІАЛЬНОГО КАПІТАЛУ ЯК КЛЮЧОВА ПЕРЕДУМОВА РОЗВИТКУ НАЦІОНАЛЬНОЇ ЕКОНОМІКИ - Todoruk, Sergy; Щурик, Михайло (My University, 2019)
Рушійною силою, що забезпечує успішний соціально-економічний розвиток кожної країни є соціальний капітал. Без безпосередньої участі людини суспільно відтворювальний процес неможливий, попри задіяність у ньому новітніх досягнень науки і техніки, запровадження сучасних технологій, інновацій тощо. В статті авторами досліджуються процеси задіяності, відтворення та участі соціального капіталу в соціально-економічному розвитку України. Особливе місце відведено мотивації соціуму до праці, атрофованим цінностям світосприйняття. Зазначено, що каталізатором забезпечення успішного розвитку країни, макрорегіонів і регіонів є довіра в суспільстві. Нині в Україні немає достатньої довіри між владними структурами і соціальним капіталом. Значне місце в дослідженні відведено цінностям пересічних громадян, олігархату. Йдеться про гроші, шляхи їх генези. Якісною характеристикою, показниками, що віддзеркалюють якість соціального капіталу є інтелект громадян, інтелектуальний капітал, який був, є і буде рушійною силою соціально-економічного розвитку любої країни. В Україні діючі засади його формування, розвитку не є достатньо сформованими. Чинна влада не приділяє незалежної уваги для його утвердження та формування як ключового чинника соціально-економічного розвитку. Вітчизняні бізнесові й провладні структури ігноруються вітчизняним інтелектуальним капіталом і віддають перевагу новаціям, які генеруються за межами нашої країни. Авторами зазначається, що генеза та використання інтелектуального капіталу гальмується освітніми та навчальними закладами, Міністерством освіти та науки України про що засвідчує щорічна зміна навчальних програм, розширення контингенту осіб для проведення ЗНО як засобу боротьби з корупцією. Критично оцінюється інтенсифікація еміграції випускників шкіл, вишів, здібної молоді, молодих учених в країни ЄС, що в кінцевому рахунку призводять до деградації соціального капіталу, недовикористання найбільш цінної компоненти національного багатства, зменшення населення української держави, загрози втрати державності. Аналізується надзвичайно мізерне фінансування державою науки, наукових досліджень. Витрати в Україні на проведення науково-дослідних робіт є одними з найменших в світі. Означене стосується також і оплати праці вчених, які працюють у вишах. Вона в рази є меншою в порівнянні з радянським періодом та матеріальною винагородою, що нині одержують вчені в країнах ЄС. В роботі пропонується відмовитись від алгоритму організації оплати праці науковців, який нині тісно прив’язаний до засад, які використовують для матеріальної винагороди вчителів шкіл, профтехучилищ тощо. Значну увагу авторами статті приділено дослідженню проблем збереження й охорони соціального капіталу, зокрема діяльності закладів охорони здоров‘я, освіти, культури й мистецтва, морально-духовному вихованню найбільш мобільної частини соціального капіталу – молоді.
MAINTENANCE AND GENESIS OF SOCIAL CAPITAL AS A KEY PRINCIPLE OF THE NATIONAL ECONOMY DEVELOPMENT
Social capital is the driving force behind the successful social and economic development of every country. Social reproduction process is impossible without the direct participation of a human being, despite the application of the latest advances in science and technology, the introduction of modern technologies and innovations, etc. The authors study the processes of envolment, reproduction and participation of the social capital in the socioeconomic development of Ukraine. A special emphasis is given to the motivation of society to work, the atrophied values of world perception. It is noted that trust in the society is a catalyst for ensuring successful development of the country, macro regions and regions. Currently, there is not enough trust between authority structures and social capital in Ukraine. A significant place in the study is devoted to the values of ordinary citizens, the oligarchy. It deals with money, the ways of their genesis. Qualitative characteristics, indicators that reflect the quality of social capital are the intelligence of citizens, intellectual capital, which has been and will be the driving force of socio-economic development of any country. The existing principles of its formation and development in Ukraine are not sufficiently formed. The current government does not pay careful attention to its approval and formation as a key factor in socio-economic development. Domestic business and government structures are ignored by domestic intellectual capital and they prefer innovations that are generated outside our country. The authors state that the genesis and use of intellectual capital is hampered by educational and academic institutions, the Ministry of Education and Science of Ukraine, as evidenced by the annual change in the curriculum, the expansion of the contingent of people for conducting External Independent Evaluation as a means of combating corruption. There being critically evaluated the intensification of the emigration to the EU countries among graduates from schools, universities, gifted young people, young scientists , which ultimately leads to the degradation of social capital, under-use of the most valuable component of national wealth, a decrease in the population of the Ukrainian state as well as the threat to lose statehood and sovereignty. There being analyzed an extremely low financing of science and scientific research by the state. In Ukraine expenditures on conducting research work are among the lowest in the world. This also concerns the salaries of scientists working at universities. It is several times less than during the Soviet period and in comparison with the material rewards that scientists receive in the EU. The article proposes to give up the algorithm of the arrangement scientists labour payment, which is now closely bound to the principles used for the material remuneration of teachers of schools, vocational schools, etc. The authors pay much attention to the problem of the maintenance and protection of social capital, in particular the activities of health care institutions, education, culture and art, and the moral and spiritual education and upbringing of youth, the most mobile part of social capital.
Keywords: народ; капітал; соціум; демографія; інтелект; міграція; незалежність; people; socium; capital; demography; intellect; migration; independence